Detecting livelock in activity diagram using process expression - Prompong Sugunnasil (2018)
© 2017 IEEE. The activity diagram is a diagram dedicated to model the flow of actions from the beginning point to the termination point. Despite the popularity, the diagram does not incorporate with the formalism. As a consequence, the result diagram could contain some errors in the structure. One the common problems is the livelock problem, a state of infinite execution. In this paper, a formal method to identify the livelock in the activity diagram is proposed. One common mathematical approach is the expression, a well-formed combination of symbol. The proposed method employs the explainability of the expression to identify the problem. The working strategy of this paper is to define a formalism using the expression and to show that the activity diagram can be converted into the proposed method. Then, the livelock will be identified through a specific operation of the expression. As a result, examples of the conversion are given and the livelock will be identified, if there is any.